2014
DOI: 10.1074/mcp.m113.037176
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin Heavy Chain in Triple Negative Breast Cancer: A Favorable Prognostic Marker that Relates to a Cluster of Differentiation 8 Positive (CD8+) Effector T-cell Response

Abstract: Ferritin heavy chain (FTH1) is a 21-kDa subunit of the ferritin complex, known for its role in iron metabolism, and which has recently been identified as a favorable prognostic protein for triple negative breast cancer (TNBC) patients. Currently, it is not well understood how FTH1 contributes to an anti-tumor response. Here, we explored whether expression and cellular compartmentalization of FTH1 correlates to an effective immune response in TNBC patients. Analysis of the tumor tissue transcriptome, complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 52 publications
3
40
1
Order By: Relevance
“…FTH1) belonging to the same signature314. While the cytoplasmic component appeared to be ubiquitous and homogeneous, as staining intensity was generally weak or moderate and present in the majority (>70%) of tumor cells, nCMPK1 displayed a higher degree of heterogeneity in terms of expression and number of stained tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…FTH1) belonging to the same signature314. While the cytoplasmic component appeared to be ubiquitous and homogeneous, as staining intensity was generally weak or moderate and present in the majority (>70%) of tumor cells, nCMPK1 displayed a higher degree of heterogeneity in terms of expression and number of stained tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the relative contributions of these T cell subsets to productive immunity against cancer, but it is feasible to assume that polyfunctional CD8 T cells will prove to be more efficient in cancer immunotherapy. Higher percentages of CD8 T cells in the tumor have been correlated with better prognosis for a variety of cancers [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al showed that over 60% of the TNBC patients who received adjuvant chemotherapy using the conventional St. Gallen 95 and NIH 96 criteria were unnecessarily treated based on the 11-proteins signature defined in this study. A subsequent proteomics study 97 further validated that FTH1, an immunomodulatory molecule involved in augmentation of CD8+ T cells in the tumour area, is a potential therapeutic target in TNBC.…”
Section: Triple-negative Breast Cancer (Tnbc)mentioning
confidence: 91%